Sri Lankan Tamil Electronic Media - Raguram, S. (My University, 2020)
Media plays a significant role in shaping the social, political, economic and cultural conditions of the Tamil community in Sri Lanka and has a substantial influence on the formation of general opinions about various issues affecting the Tamil community. More importantly, the matters expressed by media leads to the formation of opinions in different forms. The general perception about the trust about a particular media highly influences the formation of a common opinion among the masses. These opinions affect different matters in different ways. There is a significant segment of a population unable to understand the ownership, background and real motives of media organizations and do not have sufficient knowledge to undertake analysis to understand media’s influence in societies. The opinion formation trends created by media create a considerable impact among such populations. Looking at the contemporary media landscape of Sri Lanka, most of the media organizations are owned by politicians from the ruling party, other politicians and people with massive commercial backgrounds. In this backdrop, there are inevitable questions that arise about the truthfulness and impartiality of the news stories and the social responsibilities of these media outlets. The study endeavours to understand the role of media in acting as an independent source amplifying the voice of the people.
Keywords: Sri Lanka; Tamil Media; Electronic Media